2017
DOI: 10.1111/jopr.12730
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Mechanical Properties of Newly Developed Monolithic Multilayer Zirconia

Abstract: The optical and mechanical properties of the tested monolithic zirconia are material dependent. Fully stabilized monolithic zirconia materials (CZF and PA) are relatively more translucent than partially stabilized zirconia (ZT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 29 publications
7
57
3
3
Order By: Relevance
“…Increasing the cubic crystals improves zirconia's translucency owing to optical anisotropy. SEM micrographs of PRTA showed a larger grain size as compared to PRT (Figure 4), resulting in decreased grain-boundary areas, which act as a scattering source [24]. This observation is in agreement with previous studies [17,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Increasing the cubic crystals improves zirconia's translucency owing to optical anisotropy. SEM micrographs of PRTA showed a larger grain size as compared to PRT (Figure 4), resulting in decreased grain-boundary areas, which act as a scattering source [24]. This observation is in agreement with previous studies [17,25].…”
Section: Discussionsupporting
confidence: 91%
“…Kim and Kim, in their study, showed TP values for zirconia similar to the present study (Bruxzir was 10.29) [25]. However, these values were dissimilar to values reported by other authors [24,26]. Elsaka reported that the TP of Prettau Anterior as monolithic zirconia was 16.8, which was significantly lower than that for Ceramill Zolid FX (CZF) multilayer with 19.4 [24].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Flexural strength of 444 MPa, elastic modulus of 70 GPa and fracture toughness of 2.3 MPa m 1 = 2 have been reported for Vita Suprinity [23,24]. The result of a study made by Elsaka, showed fracture toughness value of 3.7 MPa m 1 = 2 and flexural strength of 676 MPa for Ceramill Zolid FX Multilayer [25]. In an in vitro study, the elastic behavior of CAD/CAM materials were compared and polycrystalline zirconia demonstrated Young's modulus and bulk modulus of 206 GPa and 134 GPa, respectively which were almost twice the values demonstrated by zirconia reinforced lithium silicate [26].…”
Section: Discussionmentioning
confidence: 94%
“…13,22 Recent study claims that multilayer monolithic zirconia has improved optical and mechanical properties than the conventional monolithic zirconia. 23 The manufacturers of zirconia dental ceramic could adopt those methods to highlight the great mechanical and physical properties of zirconia with optimal translucency for wider clinical application and esthetic satisfaction.…”
Section: Resultsmentioning
confidence: 99%